MAKSIM KUANTITAS DAN MAKSIM KUALITAS SERTA IMPLIKATURNYA PADA TAYANGAN MATA NAJWA EPISODE “IRONI HARI-HARI INI” - Pratiwi, Dyah; Assidik, Gallant Kurnia (Universitas Hamzanwadi, 2022)
This study aims to describe the observance of maxims of quantity and maxims of quality, describe violations of maxims of quantity and maxims of quality, and describe the implicatures found in Mata Najwa's episode of